Outcome and Complications of Combined Modified Deep Sclerectomy and Trabeculectomy for Surgical Management of Glaucoma: A Pilot Study - Sangtam, Tiakumzuk (Clin Ophthalmol, 2020)
PURPOSE: To report the outcome and complications of a combined surgical technique of modified deep sclerectomy and trabeculectomy (mDST) for glaucoma. PATIENTS AND METHODS: Retrospective study of 44 eyes of 43 patients with open and closed angle glaucoma who underwent mDST. Outcome measures were: Surgical Success with 3 criteria - (i) criterion 1 = intraocular pressure (IOP) ≤21 mmHg or reduced by ≥20% of pre-operative IOP or IOP ≥6 mmHg on 2 consecutive time points after 3 months; (ii) criterion 2 = IOP ≤18 mmHg or reduced by ≥30% of pre-operative IOP or IOP ≥6 mmHg on 2 consecutive time points after 3 months and (iii) criterion 3 = IOP ≤15 mmHg or reduced by ≥40% of pre-operative IOP or IOP ≥6 mmHg on 2 consecutive time points after 3 months; IOP Reduction; Use of Anti-glaucoma Medication; Complications; Visual Acuity and Postoperative Interventions. RESULTS: Median follow-up was 40 months (range 24–77 months). At the final follow-up visit, the mean postoperative IOP was 11.5 ± 4.7 mmHg (p<0.0001). Mean number of anti-glaucoma medications decreased from 2.45 ± 1.21 to 0.54 ± 0.95 (p<0.0001). Surgical success in terms of IOP reduction was 50%; 43.2%; 36.4% for the 3 criteria respectively (complete success) and 70.5%; 56.8%; 47.7% for the 3 criteria respectively (qualified success). The complications noted were shallow/flat anterior chamber in 2 (4.54%), hyphema & bleb leak in 3 (6.81%), aqueous misdirection in 1 (2.27%), hypotonic maculopathy in 2 (4.45%) and hypotony requiring intervention in 6 (13.63%) eyes. CONCLUSION: Combined mDST was found to be an effective surgical procedure in reducing IOP. It was associated with complications commonly encountered in glaucoma filtering surgery. The use of intra-scleral space maintainer may help lower the risk of flat or shallow anterior chamber during the early postoperative period.